Developing Empathy with STEAM Learning in Grade VIII SMP Lazuardi Al-Falah Depok - Febriandrini Kumala (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
Empathy (Burns and Lesseig, 2017) is a skill that is rarely discussed in planning mathematics lessons. The objective of this research is to initiate and explore how mathematics learning can develop empathy skills to students using STEAM based project. This research use qualitative method, in which the observation was executed when students were developing until launching the application prototype to a limited audience. The application created with Google Sheets was called Your Energy Counter, intended to count the energy gathered from the food consumed by the user. This research revealed how empathy was formed during the project execution and how students are able to reflect on themselves being empathetic to others during mathematics lessons.